Research progress on AMPK in the pathogenesis and treatment of MASLD - Feng, Jiang; MengHuan, Li; TingTing, Yao; XueJie, Yi; HaiNing, Gao (Frontiers in Immunology, 2025)
Metabolic dysfunction-associated steatotic liver disease (MASLD; formerly known as non-alcoholic fatty liver disease, NAFLD) has become one of the most prevalent chronic liver diseases worldwide, with its incidence continuously rising alongside the epidemic of metabolic disorders. AMP-activated protein kinase (AMPK), as a key regulator of cellular energy metabolism, influences multiple pathological processes associated with MASLD. This review systematically summarizes the regulatory roles of AMPK in lipid metabolism, inflammatory response, cell apoptosis, and fibrosis. Additionally, it discusses the latest developments of AMPK activators from preclinical to clinical studies, while analyzing the major challenges currently faced and potential strategies for resolution. A deeper understanding of AMPK regulatory mechanisms will contribute to the development of more effective therapeutic approaches for MASLD.